The Validity of Point-of-Care Test (POCT) Lateral Flow Immunochromatographic Assay (LFIA) Candida albicans for the Diagnosis of Vulvovaginal Candidiasis - Puspitasari, Monika; Retno Pudjiati, Satiti; Sri Siswati, Agnes (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Vulvovaginal candidiasis is one of the most common causes of complaints of vaginal discharge, which is mostly caused by Candida albicans. The common diagnosis of vulvovaginal candidiasis is microscopic and culture examination. However, the availability of examinations is limited at the private clinic, and for culture examinations, the cost is high and results take several days. The point-of-care test (POCT) lateral flow immunochromatographic assay (LFIA) is a tool that can detect Candida albicans antigens, but this diagnostic test has never been carried out in Indonesia. Purpose: to know the validity of POCT LFIA Candida albicans for the diagnosis of vulvovaginal candidiasis caused by Candida albicans in women with complaints of vaginal discharge. Methods: Cross-sectional observational study with a diagnostic test design, using vaginal discharge samples. Vaginal discharge samples were subjected to POCT LFIA examination with the Medomic Candida albicans/ Trichomonas vaginalis/ Gardnerella vaginalis Antigen Combo Test KitÒ and Candida spp culture. Result: POCT LFIA Candida albicans had a sensitivity of 100%, specificity of 89.9%, accuracy of 90.32 %, LR (+) 9, LR (-) 0, PPV 50%, and NPV 100% against Candida spp. culture. Conclusion: The POCT LFIA Candida albicans can be used to diagnose vulvovaginal candidiasis caused by Candida albicans in women who complain of vaginal discharge.